Anastomosis oversewing technique to prevent leakage after oesophagectomy: a propensity score-matched analysis. (19th November 2021) - Tu, De-Hao; Qu, Rirong; Ping, Wei; Yang, Guang; Fu, Xiangning; Cai, Yixin
Abstract: OBJECTIVES: Oesophagogastric anastomosis is a core part of oesophagectomy, and anastomotic leakage is among its main concerns. We used the oversewing technique to reinforce the anastomosis created with a circular stapler. This study investigated the use of oversewing to reduce the incidence of anastomotic leakage without increasing morbidity. METHODS: This study enrolled 1734 patients who underwent oesophagectomy for oesophageal cancer between April 2012 and December 2019. Using propensity score-matched analysis, the clinical results of postoperative complications were compared between anastomotic-oversewn and -unsewn oesophagectomies. RESULTS: Of the 1734 patients, 661 were included in the anastomotic-unsewn group and 661 in the anastomotic-oversewn group after propensity score matching. The clinical characteristics did not differ between the 2 groups, but the frequency of anastomotic leakage was significantly higher in the anastomotic-unsewn group than in the anastomotic-oversewn group (10.3% vs 4.7%, P  < 0.001). Multivariable logistic analysis showed oversewn anastomosis and smoking history as the independent factors associated with anastomotic leakage (odds ratios, 0.399 and 2.383; P  < 0.001 and P  = 0.012, respectively). On the sub-group analysis, the relative risk for anastomotic leakage was significantly higher with unsewn than with oversewn anastomosis in patients <65 years old, those with American Association of Anesthesiologists score II, those who had middle segment oesophageal cancer and those who have undergone the McKeown approach and cervical anastomosis. CONCLUSIONS: Anastomosis oversewing technique may be a practical method to reduce anastomotic leakage, especially in younger patients and those who have undergone the McKeown approach and cervical anastomosis. Abstract : Oesophagectomy plays a fundamental role in the radical treatment of oesophageal cancer.